A new genus of pliopithecoid from the late Early Miocene of China and its implications for understanding the paleozoogeography of the Pliopithecoidea. Issue 145 (August 2020) - Harrison, Terry; Zhang, Yingqi; Wei, Guangbiao; Sun, Chengkai; Wang, Yuan; Liu, Jinyi; Tong, Haowen; Huang, Baiting; Xu, Fan
Abstract: A diversity of pliopithecoids is known from Miocene localities in Europe, but until recently, this group was relatively poorly represented in China. However, new discoveries have shown that Chinese pliopithecoids were taxonomically diverse and geographically widespread. The earliest pliopithecoids in China (and Eurasia) are Dionysopithecus and Platodontopithecus from the Early Miocene of Sihong, Jiangsu (∼19−18 Ma). During the Middle Miocene (∼15−12 Ma), several species of pliopithecoids are recorded at localities in Gansu Province (Laogou), Inner Mongolia (Damiao), Xinjiang Uygur Autonomous Region (Tieersihabahe), and Ningxia Hui Autonomous Region (Tongxin). Finally, a late-surviving anapithecine crouzeliid, Laccopithecus robustus, is known from the Late Miocene (∼7 Ma) of Shihuiba in Yunnan, which postdates the extinction of pliopithecoids in Europe (during MN 10). Paleontological investigations at a late Early Miocene locality near Fanchang in Anhui Province have yielded a large sample of isolated teeth (more than one hundred) of a previously unknown species of pliopithecoid. The associated micromammals indicate an age contemporaneous with the Shanwang Formation in Shandong Province (MN 3–4, ∼18−17 Ma). All of the permanent teeth are represented except for I2 . With its unique suite of dental features, the Fanchang pliopithecoid can be attributed to a new species and genus. Shared derived features of the lower molars confirm that the Fanchang pliopithecoid has its closest affinities with European crouzeliids, but a number of primitive traits indicate that it is a stem member of the clade. The evidence points to China as an important center for the early diversification of pliopithecoids. Contrary to previous zoogeographic scenarios, the occurrence of an early crouzeliid in China implies that the Pliopithecidae and Crouzeliidae may have diverged from a stem pliopithecoid in Asia during the Early Miocene before their arrival in Europe.